Chemical synthesis and characterization of poly(poly(ethylene glycol) methacrylate)-grafted CdTe nanocrystals via RAFT polymerization for covalent immobilization of adenosine - Trinh Duy, Nguyen; Hieu, Vu-Quang; Thanh, Sang Vo; Duy, Chinh Nguyen; Dai-Viet, N. Vo; Dai Hai, Nguyen; Kwon, Taek Lim; Dai, Lam Tran; Long, Giang Bach (MDPI, 2019)
This paper describes the functionalization of poly(poly(ethylene glycol) methacrylate) (PPEGMA)-grafted CdTe (PPEGMA-g-CdTe) quantum dots (QDs) via surface-initiated reversible addition–fragmentation chain transfer (SI-RAFT) polymerization for immobilization of adenosine. Initially, the hydroxyl-coated CdTe QDs, synthesized using 2-mercaptoethanol (ME) as a capping agent, were coupled with a RAFT agent, S-benzyl S′ trimethoxysilylpropyltrithiocarbonate (BTPT), through a condensation reaction. Then, 2,2′-azobisisobutyronitrile (AIBN) was used to successfully initiate in situ RAFT polymerization to generate PPEGMA-g-CdTe nanocomposites. Adenosine-above-PPEGMA-grafted CdTe (Ado-i-PPEGMA-g-CdTe) hybrids were formed by the polymer shell, which had successfully undergone bioconjugation and postfunctionalization by adenosine (as a nucleoside). Fourier transform infrared (FT-IR) spectrophotometry, energy-dispersive X-ray (EDX) spectroscopy, thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy results indicated that a robust covalent bond was created between the organic PPEGMA part, cadmium telluride (CdTe) QDs, and the adenosine conjugate. The optical properties of the PPEGMA-g-CdTe and Ado-i-PPEGMA-g-CdTe hybrids were investigated by photoluminescence (PL) spectroscopy, and the results suggest that they have a great potential for application as optimal materials in biomedicine.